An Analysis of Directive Illocutionary Acts Found In Doctor Strange Movie - -, Ni Luh Dias Henisandiasari (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
Communication is a vital point in our daily lives as human beings, and as humans, we often use voice and sound to communicate. Therefore, we use speech acts every time we communicate. The type of speech act that we often use is Directive Illocutionary Act which occurs when we speak to get the listener to do something. We were not only able to spot directive illocutionary acts in daily life, but also a movie and this study aims to identify and analyze the directive illocutionary acts from a dialogue in the movie. The results of the findings show that the Doctor Strange movie contains several types of directive speech acts, such as; Asking, Telling, Urging, Commanding, Requesting, Begging, Advising, Order, Permitting, Requiring and Demanding, Recommending, Forbidding, Prohibiting, and Warning. The writer used the theory by Searle and Vanderveken (1985) to conduct the analysis and used a descriptive qualitative method to collect and analyze the data that were found.